PENDIDIKAN ANAK USIA DINI DALAM TEMBANG “CENING AYU” - Dian Saputra, I Made (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2017)
The thing which very important in the world is education. It is a very important aspect given from childhood to adulthood. In short, education is required by various groups and continue to the long period of time. These days many people are given the information related to character education. Because of character education is important to be applied. Many things that can be used as an intermediary in delivering aspects of character education. One of them is a traditional Balinese song. Balinese traditional songs have been selected as a medium of communication in the delivery of character education because in traditional songs contained lyrics which are full of meaning and moral values. Traditional songs in Bali have existed since immemorial time and without the author’s name, so people who make the lyrics to this song can be our ancestors by inserting moral values and education that we can enjoy today. One of the famous traditional songs in Bali is CeningAyu. In the lyrics of CeningAyu, there are some moral values and education including the value of responsibility, child compliance, and obedience to the commands of parents.